Developing food literacy through the health sector - Begley, Andrea (2016)
The chapter examines the alignment of science inquiry skills to the information literacy framework (Bent & Stubbings, 2011) and considers how these skills were supported by a range of web 2.0 tools using the TPACK framework to create an on-line scaffolded inquiry in two school contexts. Two case studies of inquiry around the pedagogy of ICT skills are examined here; one study in six grade seven high school classes and the other in a single extension group of twenty-five primary students from grade five to grade seven. In addition the affordances and limitations of the technology tools are assessed to determine how the scaffolded on-line inquiry process could be implemented in schools. In conclusion the chapter describes how in these cases, scaffolded on-line inquiry provides an opportunity for students to create an authentic, rich and detailed inquiry around their focus utilising a range of ICT tools and strategies.